THE DEVELOPMENT OF TECHNOLOGY AND FORMULATION OF MEAT PASTE OF TURKEY MEAT - A. S. Kambarova; A. N. Nurgazezova; M. B. Rebezov; ZH. K. Moldabaeva; G. N. Nurymkhan; ZH. M. Atambayeva; E. ZH. Arinova (Алматы технологиялық университетінің хабаршысы, 2021)
The article presents the technology of production of protein-vegetable additives, technology of meat and vegetable pate.In the meat pate, the nutritional and biological value was studied, which was compared with the control sample.Analysis of experimental data shows that the number of essential amino acids in the paste "Damdi" increases compared to the control sample, the amount of valine to 0.4 g, isoleucine to 0.3, leucine to 0.2, lysine to 0.6, metonine to 0.067, threonine to 0.267, tryptophan to 0.031, phenylalanine to 0.15.The content of the main food nutrients in the pate "Damdi" (proteins, fats, carbohydrates, ash) also exceeded the control sample, which indicates its high nutritional value.